Isolation And Characterization Of Multi-Antibiotic-Resistant E. Coli From Diarrhoeic Companion Dogs - Pundlik, M.A.; Doley, S.; Tumlam, U.M.; Awandkar, S.P.; Kesharkar, J.A.; Tembhurne, P.A.; Gohain, S.; Ingle , V.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was undertaken to investigate the virulence potential and antibiotic resistance patterns of E. coli isolated from diarrheic companion dogs. The haemolysin production was recorded in 85.71% isolates while 92.85% isolates were shown to possess CR binding ability. Both these characteristics were recorded in 85.71% isolates. In vitro antibiotic sensitivity test revealed multiple antibiotic resistances developed in these isolates. The results alarm the potential public health hazards of E. coli from companion dogs.